(untitled) (REMUNOM, 2025)
This study analyzed the stages of the materials handling process practiced by an industry that operates in the industrial hub of Manaus. It used the survey method, whose data were collected with the help of a semi-structured interview script and another script to observe the functioning of the process selected for study, constructed based on the theoretical architecture developed based on the literature review. The results showed that a) the materials handling process practiced consists of eight stages, with the first being performed outside the storage area, b) the equipment used for handling is used in specific substages to perform specific activities, and c) the functionalities of the equipment used are associated with the efforts to maintain the integrity of raw materials and products while contributing to streamlining the production process. The conclusion shows that the practice of the materials handling process contradicts the theoretical architecture developed in the first and the last stages.